Adaptation and validation of UNICEF/Washington group child functioning module at the Iganga-Mayuge health and demographic surveillance site in Uganda - Nukhba Zia; Mitchell Loeb; Dan Kajungu; Edward Galiwango; Marie Diener-West; Stephan Wegener; George Pariyo; Adnan A. Hyder; Abdulgafoor M. Bachani (BMC, 2020)
Abstract Background The UNICEF/Washington Group Child Functioning Module (CFM) assesses child functioning among children between 5 and 17 years of age. This study adapted and validated the CFM at the Iganga-Mayuge Health and Demographic Surveillance Site (IM-HDSS) in Uganda. Methods This cross-sectional study was conducted between September 2018-January 2019 at the IM-HDSS. Respondents were caregivers of children between 5 and 17 years of age who were administered modified Washington Group short set (mWG-SS) and CFM. The responses were recorded on a 4-point Likert scale. Descriptive analysis was conducted on child and caregiver demographic characteristics. Exploratory factor analysis (EFA) assessed underlying factor structure, dimensionality and factor loadings. Cronbach's alpha was reported as an assessment of internal consistency. Face validity was assessed during the translation process, and concurrent validity of CFM was assessed through comparison with disability short form. Results Out of 1842 caregivers approached, 1439 (78.1%) participated in the study. Mean age of children was 11.06 ± 3.59 years, 51.4% were males, and 86.1% had a primary caregiver. Based on EFA, vision, hearing, walking, self-care, communication, learning, remembering, concentrating, accepting change, behavior control, and making friends loaded on factor 1 - "Motor and Cognition," while anxiety and depression loaded on factor 2 - "Mood". Cronbach's alpha for the overall CFM was 0.899 (good internal consistency). Cronbach's alpha for each extracted factor was excellent, motor and cognition (0.904), and mood (0.902). CFM had acceptable face validity. Spearman's rank correlation between scores of CFM and modified WG short set was 0.51 (p-value < 0.001). The overall mean CFM score was 2.47 ± 3.82 out of 39. The mean score for Mood (1.35 ± 1.42 out of 6) was higher compared to Motor and Cognition (1.12 ± 3.06 out of 33). Comparing modified WG short set and CFM Likert responses, the percent agreement was greatest for "cannot do at all." Conclusion CFM is a two-factor, valid and reliable scale for assessing disability in Uganda and can be applied to other similar settings to contribute towards disability data from the region. It is an easy-to-administer tool that can help in deeper understanding of context-specific burden and extent of disability in children between 5 and 17 years of age.